Determinants of Healthy Aging in Internally Displaced Communities in Nigeria - Makanju, Adebayo O.M; Khan, Hafiz T.A (African Human Mobility Review, 2021)
The main objective of this research article, is to assess the effect of socio-economicand environmental determinants on the healthy aging status amongst internally displacedmigrants and non-migrants nestled within the environmentally stressed regionsof Northeastern Nigeria. Methodologically the study utilized secondary data from theNigerian IDP Survey 2018 (Location-Northeastern States; n-1293 adults aged â‰¥50;male n-63.1%, female n-36.9%) using a multi-stage stratified random sample. Variedstatistical techniques such as cross-tabulation and binary logistic regression were usedto analyze the dataset. The study results show a high mean prevalence of old-age disabilitywithin the study area, irrespective of migration status in Northeastern Nigeria.Secondly, socio-economic and environmental determinants were robust predictors oflater-life health outcomes. In addition, the regression revealed that concomitant factorssuch as age, gender and sanitation have a negative effect on older adult wellnessand well-being. Meanwhile, the migration status of internally displaced persons (IDPs),although in most cases forced, significantly improves the odds of aging healthily. Conclusively,the quality of life of the older adults, irrespective of migration status, is poorlyimpacted by diminishing familial supports, social exclusion, non-existent social securityprogram and non-existence of healthcare infrastructure. Based on the study results,we recommend that the proposed Economic Community of West African States (ECOWAS)Sahelian â€œGreen beltâ€ afforestation project targeted, especially to areas aroundthe Chad basin be fully implemented, as this project will help mediate the perennialconflicts between the herdsmen and farming communities.